An Unusual Presentation of Crohn’s Disease Diagnosed Following Accidental Ingestion of Fruit Pits: Report of Two Cases and Review of the Literature - Emanuele Sinagra; Dario Raimondo; Salvatore Marco Iacopinelli; Francesca Rossi; Giuseppe Conoscenti; Maria Angela Di Maggio; Sergio Testai; Rita Alloro; Marta Marasà; Alberto Calandra; Claudia Costanza; Serena Cristofalo; et al. (Life, 2021)
The clinical course of Crohn’s disease (CD) is often complicated by intestinal strictures, which can be fibrotic, inflammatory, or mixed, therefore leading to stenosis and eventually symptomatic obstruction. We report two cases of subclinical CD diagnosed after fruit pit ingestion, causing bowel obstruction; additionally, we conducted a narrative review of the scientific literature on cases of intestinal obstruction secondary to impacted bezoars due to fruit pits. Symptoms of gastrointestinal bezoars in CD patients are not diagnostic; and the diagnosis should be based on a combined assessment of history, clinical presentation, imaging examination and endoscopy findings. This report corroborates the concept that CD patients are at a greater risk of bowel obstruction with bezoars generally and shows that accidental ingestion of fruit pits may lead to an unusual presentation of the disease. Therapeutic options in this group of patients differ from the usual approaches implemented in other patients with strictures secondary to CD.